Systematic Characterization of Gas Phase Binary Pre-Nucleation Complexes Containing H2SO4 + X, [ X = NH3, (CH3)NH2, (CH3)2NH, (CH3)3N, H2O, (CH3)OH, (CH3)2O, HF, CH3F, PH3, (CH3)PH2, (CH3)2PH, (CH3)3P, H2S, (CH3)SH, (CH3)2S, HCl, (CH3)Cl)]. A Computational Study - Sebastianelli, Paolo (2018)
A systematic characterization of gas phase binary prenucleation complexes between H2SO4 (SA) and other molecules present in the atmosphere (NH3, (CH3)NH2, (CH3)2NH, (CH3)3N, H2O, (CH3)OH, (CH3)2O, HF, CH3 F, PH3, (CH3)PH2, (CH3)2PH, (CH3)3P, H2S, (CH3)SH, (CH3)2S, HCl, (CH3)Cl) has been carried out using the ωB97X-D/6-311++(2d,2p) method at the DFT level of theory. A relationship between the energy gap of the SA's LUMO and the partner molecule's HOMO, and the increasing number of methyl groups -CH3 in the SA's partner molecule is provided. The binding energies of the bimolecular complexes are found to be related to the electron density in the hydrogen bond critical point, the HOMO-LUMO energy gap, the nature of the hydrogen acceptor atom, and the frequencies shift of acid OH bonds. The results show how the frontier orbital compatibility determines the binding energy and that the properties of SA's OH bond which remains free of interactions are affected by the bimolecular adduct formation.